ANALYSIS OF SERVICE QUALITY AND BRAND IMAGE ON THE DECISION TO USE COURIER SERVICES - Taufik, Edi Rahmat (Management Science Research Journal, 2023)
The research aims to analyze the Quality of Service and Brand Image regarding making decisions on the use of Courier Services by PT Tiki Jalur Nugraha Ekakurir or JNE. The Research method study used quantitative research with the sample technique collection data through questionnaire. The number of samples is 120 respondents of consumers that uses the service JNE. The results of the research analysis show that the variable of Quality Service and Brand Image has a strong influence on the decision to use JNE courier services.The implications of this research can be used by company expedition in considering decisions to use courier services through brand image and service quality.